From the Pope's hand to indigenous lands Alexander VI in Spanish imperialism - Cavedon, Matthew P. (Leiden Boston Brill, 2024)
"Was the Catholic Church responsible for European imperialism? Activists say yes, the Church says no. This book examines the key papal document from 1493. It finds that the Church played no role in English colonization. However, Pope Alexander VI may have intended to bless Spanish imperialism. Either way, over the next 150 years, Spain saw its empire as a gift from him. For many imperialists and many colonial subjects, Spain received its right to rule Indigenous lands straight from the Pope's hand." -- Cover page 4
Keywords: Alexander -- VI -- Pope -- 1431-1503; Demarcation line of Alexander VI; Ligne de démarcation d'Alexandre VI